(untitled) (Dhaka University Journal of Biological Sciences, 2022)
Pigments are one of the most significant secondary metabolites produced by microorganisms. The aim of the present study was to isolate and identify pigmentproducing bacteria from the Ratargul Swamp Forest (RSF) soil, which is the one and only fresh water swamp forest of Bangladesh. Soil samples were randomly collected from 10 different quadrates (10 m x 10 m) of RSF. The pH values of the soil samples were found to be strongly acidic and ranged between 4.71 and 5.48. Bacterial load of the samples ranged from 1.33×105 to 1.93×108 cfu/g, 6.05×106 to 9.07×107 cfu/g and from 1.16×107 to 1.61×108 cfu/g on nutrient agar (NA), peptone yeast-extract glucose (PYG) agar and Luria-Bertani (LB) agar media, respectively. Interestingly, both the highest and lowest bacterial counts were observed on NA, which was 1.93×108 cfu/g and 1.33×105 cfu/g, respectively. The isolates were found to produce various pigments like yellow, red, dark orange and sweet pink during their colony developments. A total of 71 bacterial isolates were obtained of which 11 were subjected to further study. All the selected bacteria were found to be rod shaped. Out of the 11 isolates, 9 were Gram-positive and 2 were Gramnegative. Provisionally identified potential pigment producing eight bacterial isolates were identified by using molecular marker. Seven of them were matched with their conventional identification up to generic level but conventionally identified Erwinia stewartii was found to be as Aeromonas sobria. Among the 11 isolates, 8 could produce three different types of pigments namely red, yellow and dark orange during in vitro pigment production. The isolated pigment producing bacteria could be used for better biotechnological application. Dhaka Univ. J. Biol. Sci. 31(1): 1-8, 2022 (January)